2018
DOI: 10.1111/ijd.14028
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions and dermatological diseases: contributions and therapeutic advances

Abstract: Skin disease is one of the most common human diseases and affects between 30% and 70% of individuals, which requires a lot of attention to their treatments. The delivery of active pharmacological ingredients at the topical level is a challenge because of the difficulties in overcoming the mechanical barrier created by the skin and reaching greater depths, since delivery specificities are decisive for the degree of effectiveness. In this way, the nanoemulsions emerge as a potential system for the incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Thus, research on the development of new drug formulations for leishmaniasis have appealed to innovative drug delivery systems, such as nanotechnology‐based systems, to enhance the therapeutic efficacy. Nanocarriers can direct drug substances to the site of action, improving specificity, efficacy, and therapeutic index, and decreasing toxicity 45 . In this review, only two research were found using this strategy (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, research on the development of new drug formulations for leishmaniasis have appealed to innovative drug delivery systems, such as nanotechnology‐based systems, to enhance the therapeutic efficacy. Nanocarriers can direct drug substances to the site of action, improving specificity, efficacy, and therapeutic index, and decreasing toxicity 45 . In this review, only two research were found using this strategy (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Drug optimization with innovative formulations may improve performance, solubility, and permeability, among other properties, which lead to therapeutic efficacy enhancement. Nanocarriers systems can direct drug substances to the site of action, improve permeability, effectiveness, tolerability, and therapeutic index and also decrease toxic effects of antiparasitic drugs (de Souza, Oliveira, Pereira, & Soares, 2018). For VL, such properties are desirable, as it requires greater permeability and drug selectivity to reach the tissues where the parasite is hosted, such as spleen, liver, bone marrow, and lymph nodes (Thompson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoemulsions are thermodynamically and kinetically more stable than emulsions, so they have been evaluated as colloidal carriers to improve the efficacy and tolerability of some antifungal drugs. The capacity of nanoemulsions to dissolve large quantities of drugs with low solubility, their compatibility, their ability to protect drugs from enzymatic degradation and hydrolysis as well as their capacity to penetrate the deeper skin layers, turns them into ideal drug delivery vectors [143,174].…”
Section: Other Drug Delivery Systemsmentioning
confidence: 99%